(untitled) (Prostor, 2022)
Paying attention to the sustainability of houses and any effort in this direction can be extremely important in achieving more sustainable societies. In this regard, sustainability assessment tools and more specifically the certificates that are used to evaluate the sustainability of urban houses can play major roles and, therefore, present points that need to be as efficient as possible. The study is an attempt at analyzing the efficiency of BREEAM (The British Building Research Establishment Environmental Assessment Method), as one of the most advanced and highest used certificates (in the world) in the housing sector, based on the results from a systematic literature review. To achieve this goal, the scoring system used in the BREEAM International New Construction 2016 is evaluated in order to see if the credits and weightings that are assigned to the assessment issues are aligned with the trends existing in the recent literature related to urban housing sustainability. The results of a previously published systematic review of 118 recent papers are used to extract the most important factors (and their importance degrees) affecting the sustainability of urban houses on a global scale. The analysis outcome shows significant differences in the prioritization of factors and the importance degree given to each factor between the BREEAM evaluation process and the literature review factors.